Cancer immunotherapy: Killers on sterols. - Dustin, M (Nature Publishing Group, 2016)
The dream of stimulating the body's immune response to fight cancer has become a reality in the past decade. Several potent drugs have been clinically approved that block inhibitory checkpoints in the immune system, boosting the ability of the system's T cells to mount responses against a range of cancers1. Furthermore, patients' own T cells have been successfully genetically engineered to attack blood-cancer cells2. Although these studies have established the immune system as a powerful ally in cancer therapy, there are still many challenges to overcome, and further advances would increase the number of people who stand to benefit from immunotherapy. In this issue, Yang and colleagues3 (page 651) propose a way to boost the function of antitumour T cells, using a metabolic trick to increase the level of cholesterol in the cells' membranes.